2022
DOI: 10.3390/su14031804
|View full text |Cite
|
Sign up to set email alerts
|

Adult Climate Change Education Advances Learning, Self-Efficacy, and Agency for Community-Scale Stewardship

Abstract: Education per se does not necessarily foster positive environmental behaviors; rather, a complex assemblage of influences including social integration, discovering shared values, strengthening environmental identity, self-efficacy, and agency is needed to foster environmental stewardship. We examine the participant outcomes from a new adult climate education and service course, which is delivered by local organizations. The UC Climate Stewards certification course includes relationship building, social-emotion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Survey items to measure agency and self-efficacy were extracted from existing scales to ensure quantitative construct validity. Established scales used in research by Neumann, Martinez, and Martinez [68], and Nelson, Ira, and Merelender [69] aided in the measurement of both agency and self-efficacy. Two items from Doherty and Webler [40] were extracted to assist in the measurement of agency, whilst an item from Bostrom, Hayes, and Crosman [70] was utilised in the measurement of self-efficacy.…”
Section: Survey: Sampling Processing and Data Collectionmentioning
confidence: 99%
“…Survey items to measure agency and self-efficacy were extracted from existing scales to ensure quantitative construct validity. Established scales used in research by Neumann, Martinez, and Martinez [68], and Nelson, Ira, and Merelender [69] aided in the measurement of both agency and self-efficacy. Two items from Doherty and Webler [40] were extracted to assist in the measurement of agency, whilst an item from Bostrom, Hayes, and Crosman [70] was utilised in the measurement of self-efficacy.…”
Section: Survey: Sampling Processing and Data Collectionmentioning
confidence: 99%
“…Several studies suggest that dramatic messages about future climate impacts can decrease feelings of self-efficacy, whereas information about future opportunities and behavioural changes can increase it 75,76 . Climate change education programmes have been shown to increase people's feelings of self-efficacy in the face of climate change and so presumably can help to avert the sometimes-deleterious effects of climate change information on well-being 77,78 .…”
Section: Review Articlementioning
confidence: 99%
“…The link between perceived threat and climate action is based on the assessment of the ability to cope with the threat, which can be described as self-efficacy, an important predictor of behavior (Bandura, 1983; Rainear & Christensen, 2022). Self-efficacy is confidence in one’s ability to successfully handle a situation or accomplish a task (Bandura, 1977; Nelson et al, 2022). Previous research has shown that promoting PEB such as recycling and waste prevention has a positive impact on perceptions of environmental harm (Fatima & Azhar, 2021).…”
Section: Introductionmentioning
confidence: 99%